AYURVEDIC APPROACH IN NUTRACEUTICALS W. S. R. TO RASAYANA - Chaudhari, *Tejaswini Govind; Kubde, Sneha; Dive, Mukund (AYUSHDHARA, 2017)
The roots of the concept of Nutraceuticals and functional foods can be traced to the ancient Ayurvedic system of health care. The concept of Rasayana or Rejuvenation therapy is a part of eight clinical specialities of Ayurveda. The concept of promotion of health through Rasayana is based on Ayurveda pathophysiology and its understanding of health and physiological system imbalances that lead to disease development. The word Rasayana is composed of two words ‘Ras’ + ‘Ayan’. The means by which one gets the excellence of Rasa (the nourishing fluid which is produced immediately after digestion) is Rasayana. These Rasa nourishes our body and stimulates the immunity of the body and keeps us healthy. The Ayurvedic texts describe a set of rejuvenative measures i.e. Rasayana which are claimed to act as micronutrients offering protection from external and internal stressors. This ancient understanding is being reintroduced as Nutraceuticals. Nutraceuticals are natural, bioactive materials that provide demonstrated physiological benefits or reduce the risk of chronic diseases, above and beyond their basic nutritional function. This concept of promoting health and preventing disease through nutrition and special nutritional preparations has been used for millennia in Ayurveda. The term ‘Nutraceutical’ was coined by Stephen L. De. Felice, in 1989. The word is a portmanteau of ‘Nutrition’ and ‘Pharmaceutical’ and refers to extracts of foods claimed to have a medicinal effect on human health. Consumers’ demand for quality of life has fueled the nutraceutical revolution and seeking complementary or alternative beneficial products. The association of nutraceuticals with traditional medicine brings the long standing consumer acceptance. In this review article Nutraceuticals and Rasayana in Ayurveda have been correlated and discussed.